(untitled) (Journal of Comparative Social Work, 2024)
This article presents and discusses ethical issues and implications in research when building a predictive risk model for potential use in Danish child and family welfare. The idea is to build a predictive risk model in order to study whether such a model can be valuable to child and family welfare services in the assessment of risk – aimed specifically at the decision-making process regarding notifications. Based on a framework developed especially for this field, we present and discuss ethical considerations, reflections and actions in relation to four main ethical principles: non-maleficence, autonomy, justice and explicability. We hope that our reflections on these ethical challenges can inspire research – and potentially also the field of practice when taking a deep dive into the difficult field of digitalization in social work.